MANAJEMEN FASILITAS PENDIDIKAN DALAM PEMBELAJARAN SEKOLAH MENENGAH KEJURUAN (SMK) - Ahmad Aini; Ahmad Ghaniyyurahman, Ahmad Rijani, Berkatullah Amin, M. Luqman Zulfahnor Said, Syahrani (Jurnal Salome : Multidisipliner Keilmuan, 2023)
The facilities and infrastructure in schools are the most important part that must be maintained. The quality of a school can also be seen in terms of the completeness of the infrastructure it has, because the existing infrastructure will really support the learning process, academic and non-academic. Therefore, it is necessary to make efforts to provide appropriate advice and infrastructure so that learning activities run well and provide maximum results.